Dynamic enzyme docking to the ribosome coordinates N-terminal processing with polypeptide folding - Sandıkcı, Arzu; Gloge, Felix; Martinez, Michael; Mayer, Matthias P.; Wade, Rebecca C.; Bukau, Bernd; Kramer, Günter (Nature structural & molecular biology, 2013)
Nascent polypeptides undergo various cotranslational maturation steps, including N-terminal enzymatic processing, chaperone-assisted folding and membrane targeting. Kinetic analyses now demonstrate that N-terminal processing enzymes have fast ribosome binding kinetics, and premature chaperone recruitment or folding negatively affects processing efficiency, thereby separating nascent chain processing from later events.